Pola Komunikasi Santri terhadap Kiai: Studi atas Alumni Pondok Modern dan Pondok Salaf - Ana Trisya Rahmawati (Academica: Journal of Multidisciplinary Studies, 2017)
This study discusses about the communication model between santri and kiai, comparing between alumni of pesantren modern and pesantren salaf. Based on the qualitative approach, data showed that santri and kiai in the both of two pesantrens having communication, even in different model. Communication in the pesantren salaf done by direct communication (face to face), while in pesantren modern the communication must following some procedures. Alumnae from both of pesantren salaf and modern were having good relationship with kiai. In pesantren salaf, kiai has closer relationship to santri even to his/her family, while in pesantren modern the relationship of santri and kiai just like teacher to his student, the only certain students who have closer relationship to kiai.Keywords:Communication model, Pesantren, Kyai, Santri.Â